Effects of moisture accumulation in outer walls on thermal mode of premises in case of emergency heat supply - T. A. Rafalskaya (Вестник Дагестанского государственного технического университета: Технические науки, 2021)
Objective. In the case of a coupled supply of heat in a heat supply system, engineering structures act as a heat accumulator. Therefore, when calculating the premises cooling time in case of accidents in a heating network, it is necessary to take into account not only weather conditions, but also a decrease in the flow of heat from the heat supply system, since at low outside temperatures the heat loss in premises is greater than the heat supply, which will lead to the accumulation of moisture in materials of the structures. Methods. To build a model of internal conditions in premises when the heat supply system operates in emergency mode, the humidity potential theory was applied, which allows calculating the humidity mode of engineering structures under various non-periodic exposures. Results. A method for calculating moisture accumulation in outer walls of residential premises using the moisture potential theory is proposed. Conclusion. The impact of moisture accumulation on heat accumulation in outer walls and the dynamics of internal air temperature in premises under emergency conditions of the heat supply system operation has been determined.